Development of Simple Environment-Based Practical Guides for Integrated Science Subjects Using the 4-D Model - Djalo, Aloysius; Buku, Maria Novita Inya; Nau, Getrudis Wilhelmina (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2025)
This study aims to determine 1) the validity of the development of simple environment-based practicum guides in integrated science subjects using the 4-D model, 2) the practicality of the validity of the development of simple environment-based practicum guides in integrated science subjects using the 4-D model, and 3) the effectiveness of the validity of the development of simple environment-based practicum guides in integrated science subjects using the 4-D model. This research is a development research. The development model in this study is the 4-D development model which consists of 4 stages namely Define, Design, Develop and Disseminate. The results of this study indicate that the integrated science practicum guide developed has a very high validity with a percentage of 87.04%. This shows that the developed practicum guide is suitable for use in the integrated science learning process. The developed practicum guide is included in the very practical category, with an average percentage of 82.64% indicating that the developed practicum guide can increase student participation in practicum activities. The developed practicum guide can improve students' learning outcomes by 21.5% with a moderate category, indicating that the use of simple practicum guides in integrated science subjects contributes positively to the understanding of integrated science concepts and is effectively used in integrated science learning.